Brain and spinal cord metastases with seminoma: A case report. Issue 6 (30th August 2022) - Yumioka, Tetsuya; Morizane, Shuichi; Makishima, Karen; Adachi, Tadashi; Moriyasu, Emika; Iwamoto, Hideto; Hikita, Katsuya; Honda, Masashi; Umekita, Yoshihisa; Takenaka, Atsushi
Abstract : Introduction: Brain and spinal cord metastases from testicular cancer occur rarely, and metastases with seminoma are extremely rare. Case presentation: A 42‐year‐old man who was diagnosed with seminoma and multiple metastases underwent first‐line and salvage chemotherapy. Brain metastases were noted; consequently, surgery, third‐line chemotherapy, and whole‐brain irradiation were performed. Subsequently, paralysis developed, and spinal cord metastases were detected. He received fourth‐line chemotherapy but died. Pathological autopsy revealed metastases only in the spinal cord. The cause of death was considered respiratory failure due to cervical spinal cord involvement from spinal metastases. Conclusion: Brain and spinal cord metastases from seminoma are rare. Thus, similar future cases should be treated appropriately.